Unsung heroes of animation - Robinson, Chris, 1967- (Eastleigh, UK : John Libbey, 2005)
The heroes: Raimund Krumme; Stefan Schabenbeck; George Griffith; René Jodoin; Igor Kovalyov; Priit Pärn; Pjotr Sapegin; Paul Fierlinger; Michèle Cournoyer; Ryan Larkin; Brothers Quay; Piotr Dumala; Pierre Hébert; Andreas Hykade; Phil Mulloy; David Ehrlich; Steven Woloshen; Mati Kütt; Koji Yamamura; Martha Colburn; Stephanie Maxwell; J J Villard; Signe Baumane; Dennis Tupicoff; Ruth Lingford
Includes filmographies.
boek